Experiential Analysis Of Stakeholders Perception On Voluntary Corporate Disclosure Practices (International Journal of Food and Nutritional Sciences, 2022)
Voluntary disclosure of information is presentation of excess of information in addition to mandatory disclosure in form of management forecast analysis, press release, posts on company website, conferences proceedings etc. In the present paper we have tried to examine the stakeholder’s perception on quality of annual reports. For this purpose the information is derived through well-structured questionnaire from 260 respondents. Descriptive statistics was applied and It was found that majority of the respondents prefer published Annual Reports of companies for information. We have also found that the stakeholders prefer annual reports for the purpose of analyzing the financial performance of the companies and investment decision making. The stakeholder’s perception on quality of Annual Reports resulted that understandability, comparability and predictability are the most common features which have been found in the annual reports. The study recommended that the quality of annual reports is required to be enhanced in terms of reliability, relevance of information, timeliness and consistency, which can further serve the purpose of stakeholders to refer the annual reports for analyzing the financial performance of the companies and investment decision making.